Numerical Modeling Analysis of Tornadoes Using the COSMO.GR Model Over Greece - Matsangouras, Ioannis T; E. Avgoustoglou; Gofa, F.; Pytharoulis, I.; Nastos, P. T.; Bluestein, H. W. (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{The COnsortium for Small-scale MOdeling (COSMO) was formed in October 1998, and its general goal is to develop, improve and maintain a non-hydrostatic limited-area atmospheric model, while the Hellenic National Meteorological Service joined the consortium in 1999. The COSMO model has been designed both for operational numerical weather prediction (NWP) as well as various scientific applications on the meso-beta and meso-c scale. Two tornado case studies were selected to investigate the ability of COSMO model to depict the characteristics of severe convective weather, which favored the development of the associated storms. The first tornado occurred, close to Ag. Ilias village, 8 km northwestern from Aitoliko city over western Greece on February 7, 2013, while the second tornado developed close to Palio Katramio village, 8 km southern from Xanthi city over northern Greece on November 25, 2015. Although both tornadoes had a short lifetime, they caused significant impacts. The COSMO. GR atmospheric model was initialized with analysis boundary conditions obtained from the European Centre for Medium-Range Weather Forecasts (ECMWF). The resulting numerical products with spatial resolution of 0.020 degrees (similar to 2 km) over the geographical domain of Greece depicted very well the severe convective conditions close to tornadoes formation.}